Social cognition dysfunctions in neurodegenerative diseases : neuroanatomical correlates and clinical implications (2018)
Social cognitive function, involved in the perception, processing, and interpretation of social information, has been shown to be crucial for successful communication and interpersonal relationships, thereby significantly impacting mental health, well-bei